Hilirisasi Limbah Kelapa Sawit: Potensi Fraksi Tak Tersabunkan sebagai Bahan Aktif Anti-Aging dan Pelembap Alami dalam Industri Kosmetik Modern - Chantiara Farida Makussy Muini; Munir Alinu Mulki (Journal of Pharmaceutical and Sciences, 2026)
Background: The Indonesian palm oil industry generates substantial waste, one of which is Palm Fatty Acid Distillate (PFAD), which has been predominantly utilized as a low-value industrial raw material or discarded as waste. However, PFAD contains an unsaponifiable fraction rich in high-value bioactive compounds such as vitamin E (tocotrienols and tocopherols), squalene, phytosterols, and carotenoids, which possess significant potential as natural cosmetic active ingredients. Objective: This study aims to examine the potential of palm oil waste downstreaming, particularly the unsaponifiable fraction of PFAD, as a source of bioactive compounds for anti-aging and moisturizing applications in the modern cosmetics industry. Methods: This research is a Systematic Literature Review (SLR) employing a qualitative descriptive approach. Literature searches were conducted through Google Scholar, PubMed, and Science Direct databases using keywords related to palm oil waste, PFAD, and unsaponifiable fraction, with publication restrictions set for the last five years (2021–2026). From 210 initially identified articles, 9 articles were selected after screening processes based on titles, abstracts, and full-text eligibility. Data were analyzed using a descriptive meta-synthesis approach. Results: The findings indicate that PFAD contains significant bioactive compounds, with total tocotrienol reaching 2,136 ppm and vitamin E levels up to 12,282 ppm after purification processes. The most effective extraction methods were achieved through supercritical CO₂ with ethanol as a co-solvent (30.03 ± 0.03 mg/g) and ionic liquid [C₄MIM]Ac (75.41% efficiency). The bioactive compounds of the unsaponifiable fraction demonstrated potent antioxidant activity (IC₅₀ up to 23.3 ppm), which plays a role in inhibiting oxidative stress—a primary factor in premature aging—while also maintaining skin moisture through emollient mechanisms. Formulation studies revealed that nanoemulsion applications increased skin moisture from 51% to 62.5% and elasticity from 85% to 98.5%, while palm lipid-based body butter, cream, and lotion preparations exhibited good physical stability with skin-safe pH (5–6) and no irritation. Conclusion: The unsaponifiable fraction of palm oil waste has strategic potential to be developed as a modern cosmetic active ingredient, supporting the concept of a circular economy and national cosmetic raw material self-sufficiency. However, further research is still required for clinical validation of anti-aging and moisturizing effects on human skin, as well as optimization of sustainable processing technologies.